2016
DOI: 10.1038/srep30551
|View full text |Cite
|
Sign up to set email alerts
|

High throughput screening of starch structures using carbohydrate microarrays

Abstract: In this study we introduce the starch-recognising carbohydrate binding module family 20 (CBM20) from Aspergillus niger for screening biological variations in starch molecular structure using high throughput carbohydrate microarray technology. Defined linear, branched and phosphorylated maltooligosaccharides, pure starch samples including a variety of different structures with variations in the amylopectin branching pattern, amylose content and phosphate content, enzymatically modified starches and glycogen wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…Comprehensive Microarray Polymer Profiling (CoMPP) combines the high-throughput capacity of the microarray with the specificity of monoclonal antibodies (mAbs) and carbohydrate-binding modules (CBMs), to characterize plant cell walls glycomic profiles [5,6]. Through this approach, it is possible to study the relative abundance of, and interactions between, hundreds or thousands of molecules simultaneously, using very small volumes of plant extracts.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive Microarray Polymer Profiling (CoMPP) combines the high-throughput capacity of the microarray with the specificity of monoclonal antibodies (mAbs) and carbohydrate-binding modules (CBMs), to characterize plant cell walls glycomic profiles [5,6]. Through this approach, it is possible to study the relative abundance of, and interactions between, hundreds or thousands of molecules simultaneously, using very small volumes of plant extracts.…”
Section: Introductionmentioning
confidence: 99%
“…3.2.1.3). This variant of CBM20 has a very strong affinity for starch and α-glucan (Tanackovic et al , 2016). We added an N-terminal transit peptide (TP) from barley granule-bound starch synthase (GBSSIa) as previous studies have shown that this TP effectively targets the transgenic proteins to plastids, and that it is effectively cleaved off during passage of the protein over the plastid envelope membranes (Carciofi et al , 2012 b ; Hebelstrup et al , 2017).…”
Section: Resultsmentioning
confidence: 99%
“…CBM20 is one of these SBDs, and entries with CBM20 modules are reported from organisms with broad phylogenetic diversity, including archaea, bacteria, and eukaryotes (Christiansen et al , 2009). The CBM20 used in the present study was the 12 kDa starch-binding domain (residues 509–616) of glycoamylase from Aspergillus niger , which was chosen based on a specific and high affinity for starch (Tanackovic et al , 2016). The affinity of CBM20 for starch is also significantly higher than that of the barley starch synthases GBSSI, SSI, SSIIa, SSIIIa, and SSIV (Cuesta-Seijo et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these chemical and physical methods cannot compete with the pattern recognition that is displayed in nature. Enzymes are by far, the most sophisticated tools available for pattern recognition in polysaccharide molecules Tanackovic et al, 2016). Enzymes are therefore often used instead of, or in combination with, traditional methods for the characterization of polysaccharides.…”
Section: Introductionmentioning
confidence: 99%